Nanohybrid Scaffold of Chitosan and Functionalized Graphene Oxide for Controlled Drug Delivery and Bone Regeneration - Mahanta A.K.; Patel D.K.; Maiti P. (My University, 2025)
Nanohybrid scaffolds of chitosan have been designed for controlled drug delivery and bone regeneration. Sulfonated graphene oxide has been used to develop the nanohybrids. Nanohybrid scaffolds show highly hydrophilic character and greater mechanical strength as compared to pure chitosan. Nanohybrid scaffolds show an interconnected uniform porous network structure exhibiting sustained release kinetics of the antibacterial drug, tetracycline hydrochloride. Nanohybrids are found to be highly biocompatible in nature and are able to support and proliferate MG63 osteoblast cells and thereby induce bone tissue regeneration. The in-vivo bone healing study shows that the developed nanohybrid scaffolds have the potential to regenerate the bone faster without any side effects as compared to pure scaffolds. Hence, the developed nanohybrid scaffold has good potential as a controlled drug delivery vehicle and in bone tissue engineering for faster healing. Copyright © 2019 American Chemical Society.